A case study of leadership initiatives in a diverse charter school: values in agreement and conflict. Issue 6 (2nd November 2022) - Badger, James
ABSTRACT: This case study offers an in-depth analysis of the initiatives implemented by a principal in an intentionally diverse charter school. Through extensive interviews with the principal, assistant principals, classroom teachers, and data gathered from surveys, classroom observations, and school documents, this research identifies the successful initiatives and challenges implemented by an experienced principal to affect curricular change and policies in a charter school committed to equity, social justice, and educational excellence. In this research, Lukes' theoretical framework of power was applied to examine the leadership of a charter school principal. Lukes' conceptualization provides a model to analyze power in a social system and determine how an individual exerts power, whether consensus or conflict exists or it is not observable. Findings from this case study identify a charter school principal's circumscribed role of leadership to affect change and propose a governing structure for charter schools that reframes the roles and responsibilities for those in positions of leadership.